Sujeito, espaço e identidade: configurações do homoerotismo em O filho da mãe e Simpatia pelo demônio, de Bernardo Carvalho - Silva, Alex Bruno da (2021)
The present thesis aims to analyze how the relationship between the subject and space, in the no-vels O Filho da Mãe (2009) and Simpatia pelo demônio (2016), by the contemporary writer Ber-nardo Carvalho, explains the conflicts around identity issues. We start from the hypothesis that displacement – whether represented by traffic, the wandering of characters, the crisis and fluidity of identities – brings to the forefront deviant identities that, in various aspects, call into question the crisis of the masculine, challenging heteronormative boundaries and their arrangements within discursive mechanisms. In this sense, Bernardo Carvalho, in these two novels, presents wandering/foreigner characters whose representation revolves around issues of homoeroticism and the demands of desire in different social and geographical contexts. Works analysis from the perspective of homoerotic desire, allowed this articulation between space and non-heteronormative identity to be verified, from a corporeal sociability of the characters, implying, therefore, in a literature open to difference. The methodology of this research, which is bibliogra-phical in nature, includes the theoretical-critical studies formulated by: Stuart Hall (2003/2006/2014), Regina Dalcastagnè (2012), Néstor García Canclini (2016), Michel de Certeau (2014), Tim Cresswell (2006), Doreen Massey (2015), Marc Augé (1994/2006/2010), Judith Bu-tler (2008/2015/2019), Michel Foucault (1981/2010/2014/2018/2019a/2019b/2020), Guacira Lo-pes Louro (2010/2020), among others. Thus, we hope that the results will contribute to the critical fortune of Bernardo Carvalho's fictional work, specifically, on the novels O filho da Mãe and Simpatia pelo demônio.